2009
DOI: 10.5194/osd-6-953-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting marine hazardous substances and organisms: sensors for pollutants, toxins, and pathogens

Abstract: Abstract. Marine environments are influenced by a wide diversity of anthropogenic and natural substances and organisms that may have adverse effects on human health and ecosystems. Real-time measurements of pollutants, toxins, and pathogens across a range of spatial scales are required to adequately monitor these hazards, manage the consequences, and to understand the processes governing their magnitude and distribution. Significant technological advancements have been made in recent years for the detection an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 117 publications
0
40
0
Order By: Relevance
“…The development of multi-wavelength fluorescence sensors has gained interest due to a broader application range while limiting the integration costs. Inspired by the success of laboratory based excitation-emission-matrix fluorescence spectroscopy (EEMS) [5], NeXOS will proceed from multiwavelength to matrix-fluorescence in situ sensing. Initial setup will follow a combination of three excitation and four emission wavelengths in one sensor unit, resulting in a 3x4 matrix-fluorescence unit.…”
Section: Optical Sensorsmentioning
confidence: 99%
“…The development of multi-wavelength fluorescence sensors has gained interest due to a broader application range while limiting the integration costs. Inspired by the success of laboratory based excitation-emission-matrix fluorescence spectroscopy (EEMS) [5], NeXOS will proceed from multiwavelength to matrix-fluorescence in situ sensing. Initial setup will follow a combination of three excitation and four emission wavelengths in one sensor unit, resulting in a 3x4 matrix-fluorescence unit.…”
Section: Optical Sensorsmentioning
confidence: 99%
“…Either they use optics, acoustics or electrochemical techniques [1][2]. In NeXOS, large innovative and variable coverage potential, compatibility with several platforms, as well as relevant synergies have been identified in optical and acoustical sensor systems and a critical mass of expertise was brought together to be able to bring significant progress.…”
Section: A Sensor Innovationsmentioning
confidence: 99%
“…They also play an important role in carbon cycle and export 2. With an estimated figure of over one million species of marine life (excluding bacteria), the majority of which remain to be discovered Census of Marine Life : www.coml.org…”
mentioning
confidence: 99%
“…Marine‐derived fungi form a group of potential contaminants for marine bivalves such as mussels (Zvereva and Vysotskaya ; Zielinski et al . ). In previous studies, it has been shown that Penicillium strains sampled from shellfish‐farming areas produced roquefortine C and patulin (Vansteelandt et al .…”
Section: Introductionmentioning
confidence: 97%